Odpowiedź :
Odpowiedź:
a) -5(3a + b – 2c) = -15a - 10 b + 10 c
b) 2(x – 3y) – 3(x – y) – 5(4x +3y) = 2x - 6y -3x + 3y - 20 x - 15 y = - 21x - 18 y
c) (4 – 2x)٠(6x - 8) = 24x - 32 - 12x^2 + 16 x = -12x^2 + 40 x - 32
d) (4x + 3)٠(-2x² - 3x + 1) = - 8 x^3 - 12x^2 + 4x - 6x^2 - 9x + 3 =
= -8x^3 - 18x^2 - 5x +3
e) (3 - x)٠(2 + 3x) – (2 – 5x)٠(3 + 2x) =6 + 9x - 2x - 3x^2 - (6 + 4x - 15x - 10x^2) = 6 + 7x - 3x^2 - 6 + 11x + 10x^2 = 7x^2 + 18x
Odpowiedź:
[tex]a)\ \ -5(3a+b-2c)=-15a-5b+10c\\\\\\b)\ \ 2(x-3y)-3(x-y)-5(4x+3y)=2x-6y-3x+3y-20x-15y=\\\\=-21x-18y\\\\\\c)\ \ (4-2x)(6x-8)=24x-32-12x^2+16x=-12x^2+40x-32\\\\\\d)\ \ (4x+3)(-2x^2-3x+1)=-8x^3-12x^2+4x-6x^2-9x+3=-8x^3-18x^2-5x+3\\\\\\e)\ \ (3-x)(2+3x)-(2-5x)(3+2x)=6+9x-2x-3x^2-(6+4x-15x-10x^2)=\\\\=6+7x-3x^2-6-4x+15x+10x^2=7x^2+18x[/tex]